Thinking visually for illustrators - Wigan, Mark. (New York : Fairchild Books, 2014)
"Thinking Visually for Illustrators features a wide range of work, demonstrating diverse visual languages, context, ideas, techniques and skills. It also looks at the ways in which illustrators develop their own personal visual language. Contemporary illustrators from all over the world engaged in a diverse range of approaches to the discipline have contributed their artwork and commentaries on visual thinking and the working process. The text also features the work of recent graduates, present students and observations from educators past and present. This edition has been updated to include a new chapter on illustration for the digital context and new approaches to working"--
Getting Started -- Ideas generation -- Research -- Sketchbooks -- Inspiration -- Ways of Drawing -- A history of illustration -- Outsider art -- The portrait -- Life drawing -- Experimenting -- Print workshop -- Cross-media and cultural cut-ups -- Types of Illustration -- The decorative -- Social comment -- Caricature -- Reportage -- Underground urban street art -- Storytelling -- Fantastic worlds -- The New Digital Paradigm -- The next big thing in illustration -- The future is now -- Flexibility -- A Career in Illustration -- Collaboration -- Briefs and deadlines -- Industry insights -- Conclusion.
Includes bibliographical references and index.
Keywords: Drawing, Psychology of; Thought and thinking; Information visualization; Visual communication; Communication in design; Illustrators -- Vocational guidance; DESIGN / Graphic Arts / Illustration